Analytical Analysis of the Mechanism and Mitigation Methods of Transient Overvoltage in Direct-Drive Wind Turbine Generators Connected to Weak Power System - Xu Tian; Shengtao Wu; Luran Wei; Lixin Zhang; Nan Wang; Quan Zheng (IEEE Access)
In regions with extensive wind power collection, the grid’s robustness diminishes, and transient overvoltage phenomena during the restoration phase following an AC short-circuit fault pose significant challenges to secure and stable operation. Addressing this issue, this paper establishes a mathematical model for the grid-connected system of direct-drive wind turbine generators. The expression of the terminal current is derived in detail, the impact of the inner current control loop is considered, leading to a specific expression for transient overvoltage. A comprehensive analysis is then conducted to identify various influencing factors of transient overvoltage, including grid short-circuit ratio, active power recovery speed, reactive current increment, and the response speed of the inner current loop. The conclusion is that a smaller short-circuit ratio results in a larger voltage drop and reactive current increment, which in turn leads to a higher transient overvoltage. Additionally, a slower active power recovery rate corresponds to a slower overvoltage recovery speed. Based on this analysis, an analytical control parameter optimization method is proposed to mitigate the amplitude and recovery speed of fault recovery overvoltage under various short-circuit ratios. Ultimately, a simulation model was developed within the PSCAD/EMTDC platform, and the accuracy of the transient overvoltage formulation was substantiated via analytical case studies. Furthermore, the effectiveness of the proposed method for mitigating fault recovery overvoltage was confirmed through rigorous simulation.